INTIMIDATING-SHYNESS PROCESS ON THE BUILDING OF STUDENTS PERSONALITY: REFLECTIONS ON LUDO-PEDAGOGICAL INTERVENTIONS AT SCHOOL - Pires Felix, Tatiane da Silva [UNESP]; Tuim Viotto Filho, Irineu Aliprando [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This paper is a synthesis of our dissertation, which aimed to understand critically the reality of individuals with timid characteristics at school, understanding the shyness as a historical-cultural process, which is the synthesis of multiple determinations and social relations. We understand the shyness as an intimidation-shyness process which social intimidation processes results on the development of emotions and feelings related to fear and shame, which constitute shyness. In our research, we conducted systematic observations of social relations of students of 2nd year of elementary school of 1 degrees cycle (intervals, classroom, indoor physical education and courtyard). We also observed the relationship of these students at intervention work carried out by our research group at school. Our knowledge, the intimidation situations present in the school may result in experiences consistituted of fear and shame emotions, which can contribute to the formation of the personality of students on a timid/intimidated way.
Keywords: Shyness; Intimidation; Emotions and feelings; Cultural-historical theory; Education